Introduction: Crossing the Lines? Local actors’ responses to developmental challenges in Africa - Sanches, E.; Neto, P.; Noyoo, N. (Cadernos de Estudos Africanos, 2021)
Enduring colonial legacies continue to shape contemporary politics and policies in Africa. As former and new actors seek to expand economic and political influence in the continent, new forms of domination arise to accommodate neo- and post-colonial agendas. Development, an all-encompassing word that foresees linear pathways towards socially and politically engineered goals, has been used as normative justification for such endeavours (see Escobar, 2011; Ferguson, 1994). The underlying message being that those in the Global South need to modernize and come closer to the development standards of those in the Global North (Alemazung, 2010; Easterly, 2007; Ferguson, 2006; Rist, 2007).